A categorical approach to graded fuzzy topological system and fuzzy geometric logic with graded consequence. Issue 1 (2nd January 2022) - Jana, Purbita; Chakraborty, Mihir K.
Abstract : A detailed study of graded frame, graded fuzzy topological system and fuzzy topological space with graded inclusion is already done in our earlier paper. The notions of graded fuzzy topological system and fuzzy topological space with graded inclusion were obtained via fuzzy geometric logic with graded consequence. As an offshoot, the notion of graded frame has been developed. This paper deals with a categorical study of graded frame, graded fuzzy topological system and fuzzy topological space with graded inclusion and their interrelation.